2019
DOI: 10.1186/s12199-019-0766-z
|View full text |Cite
|
Sign up to set email alerts
|

A descriptive study of solitary death in Yokohama City

Abstract: BackgroundThe solitary death rate in Japan is expected to continue increasing because of its growing super-aged society and the rapid growth of home care in the country. To accurately determine the actual status of solitary deaths, we used a novel analysis method of combining vital statistics and ambulatory care information in Yokohama City.MethodsData of persons who died at home in 2013 were obtained from death certificate notifications. We also obtained the emergency transportation records that matched the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 19 publications
(14 reference statements)
4
7
0
Order By: Relevance
“…This discrepancy depends on regional differences. In contrast, in line with our observations, PMI of solitary death cases tended to be longer in men than in women 6, 13,15,22,23,29,30 . It is important that social exclusion is closely related to solitary and isolated deaths.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This discrepancy depends on regional differences. In contrast, in line with our observations, PMI of solitary death cases tended to be longer in men than in women 6, 13,15,22,23,29,30 . It is important that social exclusion is closely related to solitary and isolated deaths.…”
Section: Discussionsupporting
confidence: 91%
“…Alcoholic liver disease, alcoholism, and schizophrenia were more frequent in men than in women. In line with this, previous studies have reported a higher prevalence of hypertension and alcoholrelated disease in solitary death cases 9,12,23,26,30 . Our results are consistent with this nding.…”
Section: Discussionsupporting
confidence: 79%
“…Indeed, cardiovascular or alcohol-related issues are emerging as key predictors of kodokushi in conjunction with being male, in the 60-79-year-old age group, are in the lower-income bracket, and living alone. A vast majority of attended death at home is attributed to malignant neoplasm in urban Japan, while a majority of examined deaths, where the cause of death is not immediately obvious and the medical examiners prepared death certificates, are attributed to cardiovascular diseases (Kakiuchi et al 2019b;Osone 2016;Tomoyuki 2009) and diseases associated with alcoholism such as hepatic cirrhosis (Kakiuchi et al 2019a;Kanawaku 2018;Morita et al 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the average PMI was the longest in the 50-59 (8.74 days) and 60-69 (7.87 days) age groups (Morita et al 2015). Similarly, a study from Yokohama, which defined solitary death as PMI-f ≥ 3 days, suggests that males and unmarried individuals were at greater risk of solitary death, whereas being ≥ 65 years of age or senility were not predictive factors (Kakiuchi et al 2019a). These studies also suggest that those with an underlying alcohol-related (Morita et al 2015) or hepatic disease (Kakiuchi et al 2019a) are at greater risk of solitary death.…”
Section: Introductionmentioning
confidence: 99%
“…The social isolation of older people is an important public health issue [ 10 , 11 ]. Addressing it requires the implementation of measures to incorporate solitary older people into the local community.…”
Section: Solitary Death and Public Health Policymentioning
confidence: 99%